Implications of notch signaling in duchenne muscular dystrophy - Den Hartog, Lily; Asakura, Atsushi (Frontiers in Physiology, 2022)
This review focuses upon the implications of the Notch signaling pathway in muscular dystrophies, particularly muscular dystrophy including Duchenne muscular dystrophy (DMD): , a pervasive and catastrophic condition concerned with skeletal muscle degeneration. Prior work has defined the pathogenesis of DMD, and several therapeutic approaches have been undertaken in order to regenerate skeletal muscle tissue and ameliorate the phenotype. There is presently no cure for DMD, but a promising avenue for novel therapies is inducing muscle regeneration via satellite cells (muscle stem cells). One specific target using this approach is the Notch signaling pathway. The canonical Notch signaling pathway has been well-characterized, and it ultimately governs cell fate decision, cell proliferation, and induction of differentiation. Additionally, inhibition of the Notch signaling pathway has been directly implicated in the deficits seen with muscular dystrophies. Here, we explore the connection between the Notch signaling pathway and muscular dystrophies including DMD, and how Notch signaling may be targeted to improve the muscle degeneration seen in muscular dystrophies.